Evaluation of trans thoracic invasive diagnostic procedures in 50 adult patients of mediastinal diseases - Biswas, Siddhartha; Saha, Rama; Deb, Jaydip; Dey, Prothoma (International Journal of Medical Research and Review, 2019)
Introduction: Mediastinum is a “Pandora’s box” with many neoplastic and nonneoplastic lesions. Clinico-radiological pattern of mediastinal diseases depends on the size, location and etiology. Hence, non-invasive approach to these cases sometimes leads to diagnostic dilemma. Aims: A prospective study was performed over a 1-year period with the objective of evaluation of diagnostic yields and risk of trans thoracic ultra sound (TTUS) and computed tomography (CT) guided fine‑needle aspiration cytology (FNAC) and Tru-cut biopsy along with comparison of cost-effectiveness among mediastinal diseases where clinical and non-invasive imaging could not conclude the diagnosis. Materials and Methods: A prospective study of mediastinal diseases of the adult population without having any diagnosis admitted in a tertiary care hospital in Eastern India was performed after clearance of the ethical committee of the institute. Fifty cases of mediastinal diseases were seen during the study period. One patient sometimes had undergone more than one procedure. The choice of a procedure depended upon the location of the lesion, nature of disease and complication and cost effectiveness ofthe procedures. During the calculation of diagnostic yield of procedure, conclusive results and concordant results to more invasive procedures were considered. Results: Among 50 patients diagnostic yield of TTUS guided FNA and Tru-cut biopsy were 60% and 63.6% respectively. Diagnostic yield of Thoracic CT guided FNA and Tru-cut biopsy were 85% and 92.3% respectively. As a whole TTUS guided invasive procedure and Thoracic CT guided invasive procedure had a diagnostic yield of 61.5% and 87.9% respectively. Complication is less in CT guided invasive procedures (9.1%) compared to Transthoracic USG guided invasive procedures (11.5%) and complication is more common in Tru-Cut biopsy (16.7%) than fine needle aspiration (5.7%). Conclusion: Tru-cut biopsy if applicable is much superior to FNAC for a definite diagnosis of the mediastinal diseases. TTUS guided invasive procedures are very much cost-effective and have added advantage of real time guidance and is comparable with CT guided invasive procedures in respect to risk and diagnostic yields.